2006
DOI: 10.1016/j.appet.2006.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Food neophobia in the context of a varied diet induced by a weight reduction program in massively obese adolescents

Abstract: Previous studies in humans have shown that short to middle-term pre-exposure to multiple foods can reduce the negative response to novel foods (neophobia). In order to explore the effects of a long-term exposure to varied foods on food neophobia, we studied a population of obese adolescents observed in a longitudinal protocol in which the multiple food experiences are induced by a residential weight reduction program (WRP) that encourages the consumption of a wide variety of foods. Seventy-two massively obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 38 publications
4
36
1
3
Order By: Relevance
“…There is evidence that the trait of food neophobia is rather stable, although behavioral food neophobia, dependent on a particular situation, can be more transient (McFarlane and Pliner, 1997;Meiselman et al 1999;Pliner and Salvy 2006;Rigal et al 2006;Reverdy et al 2008;Mustonen and Tuorila 2010). The scale used in the present study, the FNS, measures the trait food neophobia rather than the behavioral food neophobia (Pliner and Hobden 1992;Pliner and Salvy 2006).…”
Section: Genetic Architecture Of Food Neophobiamentioning
confidence: 95%
“…There is evidence that the trait of food neophobia is rather stable, although behavioral food neophobia, dependent on a particular situation, can be more transient (McFarlane and Pliner, 1997;Meiselman et al 1999;Pliner and Salvy 2006;Rigal et al 2006;Reverdy et al 2008;Mustonen and Tuorila 2010). The scale used in the present study, the FNS, measures the trait food neophobia rather than the behavioral food neophobia (Pliner and Hobden 1992;Pliner and Salvy 2006).…”
Section: Genetic Architecture Of Food Neophobiamentioning
confidence: 95%
“…Therefore, more data on food neophobia among Koreans is needed. Also, the development of the FNS has promoted an increase in research on food neophobia but has only focused on the relationship between appetite and food aversion (Arvola, Lähteenmäki, & Tuorila, 1999;Midkiff & Bernstein, 1985;Nordin, Broman, Garvill, & Nyroos, 2004;Raudenbush, Schroth, Reilley, & Frank, 1998) or on eating behavior related to adolescents and children (Dovey, Staples, Gibson, & Halford, 2008;Galloway, Lee, & Birch, 2003;Rigal et al, 2006). There is very little published research on product development or food service areas.…”
Section: Introductionmentioning
confidence: 96%
“…Studies by Pliner, Pelchat, and Grabski (1993) and Loewen and Pliner (1999) have shown the positive effect of prior exposure to good-tasting novel foods on food neophobia. Rigal et al (2006) reported an increase in mean food liking scores of a population of obese adolescents enrolled in a 9-month residential weight program (WRP) that encouraged the consumption of a wide variety of foods.…”
Section: Introductionmentioning
confidence: 98%